The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1182/blood-2006-02-004580
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of imatinib mesylate, dasatinib (BMS-354825), and nilotinib (AMN107) in an N-ethyl-N-nitrosourea (ENU)–based mutagenesis screen: high efficacy of drug combinations

Abstract: BMS-354825 (dasatinib) and AMN107 (nilo-tinib

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
318
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(332 citation statements)
references
References 34 publications
11
318
0
3
Order By: Relevance
“…88 We tested several known PDGFR inhibitors for their activity against the imatinib-resistant T674I mutant form of FIP1L1-PDGFRa using a cellular screen in Ba/F3 cells (Table 7). PKC412, a potent FLT3 inhibitor that is in clinical development for the treatment of AML, was the first inhibitor to be identified with activity against the FIP1L1-PDGFRa T674I mutant.…”
Section: Spotlightmentioning
confidence: 99%
“…88 We tested several known PDGFR inhibitors for their activity against the imatinib-resistant T674I mutant form of FIP1L1-PDGFRa using a cellular screen in Ba/F3 cells (Table 7). PKC412, a potent FLT3 inhibitor that is in clinical development for the treatment of AML, was the first inhibitor to be identified with activity against the FIP1L1-PDGFRa T674I mutant.…”
Section: Spotlightmentioning
confidence: 99%
“…In June 2006, the patient showed a white blood count of >60 000 cells/mm 3 with numerous blasts. Resistance to nilotinib in patients with the E255K mutation was predicted by in vitro studies (Bradeen et al, 2006) and recently observed in patients (Quintas-Cardama et al, 2007). It resulted in rapid dramatic increase of mutated leukemic cells.…”
Section: Resultsmentioning
confidence: 88%
“…Consequently, new kinase inhibitors are being developed that are active against imatinib-resistant mutants. Although these new inhibitors have a broad spectrum of activity against imatinib-resistant BCR-ABL variants, they remain ineffective against a handful of mutants and will elicit their own unique set of resistant mutations (Bradeen et al, 2006;Talpaz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the 5-year analysis of the IRIS data, a CCyR at 12 months was associated with freedom from progression to accelerated phase (AP) or blast crisis (BC) in 97% of patients at 60 months follow-up compared with 81% of patients without a major cytogenetic response (0%-35% Ph ϩ metaphases) (P Ͻ .001). 1 In a large single-institution analysis of 204 consecutive newly diagnosed CP-CML patients treated with imatinib, CCyR at 12 months was associated with better OS 98.0% versus 74.1% (P ϭ .03) and progression-free survival (PFS) 96.0% versus 74.0% (P ϭ .007), respectively, compared with those not achieving CCyR. 2 Moreover, patients with a partial cytogenic response at 12 months (1%-35% Ph ϩ metaphases) also had poorer PFS (82%, P ϭ .01).…”
Section: Clinical Response Depth Of Response and The Impact On Disementioning
confidence: 99%